2021
DOI: 10.3389/fneur.2021.721502
|View full text |Cite
|
Sign up to set email alerts
|

Severe Multiple Sclerosis Relapse After COVID-19 Vaccination: A Case Report

Abstract: We describe a case of acute relapse in a woman with Multiple Sclerosis (MS) shortly after the mRNA COVID-19 vaccination. The patient received a diagnosis of MS in November 2016 at the MS Centre of the A. Cardarelli Hospital (South of Italy). Since that moment, her clinical conditions and pharmacological therapies have been managed at this MS centre where, according to national recommendations, in April 2021, the patient received the BNT162b2 vaccine. Almost 48 h after receiving the vaccine, the patient develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 13 publications
(13 reference statements)
1
36
0
1
Order By: Relevance
“…This association warrants further systematic investigation, as COVID-19 vaccination, and in our cases mRNA vaccination, appears to be associated with inflammatory MS disease activity. In real-world safety reports based on MS, MOG antibody disease, neuromyelitis optica spectrum disorder, and transverse myelitis populations (963 patients), exposure to Pfizer-BioNTech COVID-19 vaccine has been associated with new or worsening neurological symptoms in less than ~15% of patients, commonly occurring early in the post-vaccination period (<7 days), and mostly self-resolving within 2 weeks ( Lotan et al, 2021a ; Lotan et al, 2021b ), Although there is evidence of immune activation with vaccines leading to other neuroimmunological disorders such as Guillain-Barré Syndrome, acute disseminated encephalomyelitis, or transverse myelitis, this has not been the case for MS. ( Stone et al, 2019 ; Agmon-Levin et al, 2009 ) Despite broad use of mRNA COVID-19 vaccines, there have been few reports of MS flares in the short-term post-vaccination period as well as optic neuritis and transverse myelitis ( Maniscalco et al, 2021 ; Kaulen et al, 2021 ). A cohort of 555 MS patients receiving at least one dose of Pfizer-BioNTech mRNA COVID-19 vaccine did not experience an increase in relapse rate as compared to the unvaccinated population ( Achiron et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This association warrants further systematic investigation, as COVID-19 vaccination, and in our cases mRNA vaccination, appears to be associated with inflammatory MS disease activity. In real-world safety reports based on MS, MOG antibody disease, neuromyelitis optica spectrum disorder, and transverse myelitis populations (963 patients), exposure to Pfizer-BioNTech COVID-19 vaccine has been associated with new or worsening neurological symptoms in less than ~15% of patients, commonly occurring early in the post-vaccination period (<7 days), and mostly self-resolving within 2 weeks ( Lotan et al, 2021a ; Lotan et al, 2021b ), Although there is evidence of immune activation with vaccines leading to other neuroimmunological disorders such as Guillain-Barré Syndrome, acute disseminated encephalomyelitis, or transverse myelitis, this has not been the case for MS. ( Stone et al, 2019 ; Agmon-Levin et al, 2009 ) Despite broad use of mRNA COVID-19 vaccines, there have been few reports of MS flares in the short-term post-vaccination period as well as optic neuritis and transverse myelitis ( Maniscalco et al, 2021 ; Kaulen et al, 2021 ). A cohort of 555 MS patients receiving at least one dose of Pfizer-BioNTech mRNA COVID-19 vaccine did not experience an increase in relapse rate as compared to the unvaccinated population ( Achiron et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only two cases of acute relapse after COVID-19 vaccination have been reported so far (13,14), both having a good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Maniscalco et al reported a case of MS relapse after the messenger ribonucleic acid (mRNA) COVID-19 vaccine. The patient reported weakness and paresthesia after 48 hours of the first dose of vaccine and responded well to methylprednisolone [9].…”
Section: Discussionmentioning
confidence: 95%